Person-centred care for dementia patients (back-end system migration and development) - Chan, Elliot Hui De (Nanyang Technological University, 2024)
Dementia is a neurological disease that affects a person’s mental abilities and can severely hinder their ability to perform daily tasks. While dementia affects people of all ages, the likelihood of getting dementia increases in the later ages of one’s life [1]. This combined with an ageing population problem in Singapore could lead to dementia patients overwhelming the current system Singapore has to care for these patients. Person-Centred Care (PEAR) is an application that helps alleviate the burden of caretakers who are primarily focused on dementia patients. The PEAR application provides many features that aim to improve the communication and coordination of a care facility and improve the quality of care that the patients are receiving. The PEAR application was previously hosted on an external web hosting provider and the School of Computer Science and Engineering (SCSE) has requested the PEAR project team to migrate the PEAR application to NTU-hosted servers. This report outlines the steps that were undertaken to accomplish the migration, as well as any challenges that were faced during this process. The report also includes a discussion on some areas that the author believes can be worked on in the future as well as some areas of improvement.